Local generation of love surface waves at the edge of a 2D alluvial valley (2018)
This work deals with the local generation of Love surface waves at the edge of an alluvial valley that is formed by a soft layer with dipping interface. These waves are extracted from the system response due to the incidence of antiplane SH plane waves. The indirect boundary-element method (IBEM) is used for computations. Results are given as modal emission spectra of Love waves, as functions of frequency, for the fundamental mode and the first two harmonics for various combinations of incidence angles, interface geometries, and impedance ratios. The structure of these emission spectra is inspired by the analytical solution of the canonical antiplane problem of a semi-infinite layer with a moving base and wall, which allows indication of the 1D response and the locally generated surface waves. © 2018, Seismological Society of America. All rights reserved.